An ecological momentary assessment of weight stigma among weight loss participants. (August 2019) - Carels, Robert A; Rossi, James; Solar, Chelsey; Selensky, Jennifer C
This investigation explored experiences of weight stigma using momentary, real-time diary assessments among adults seeking weight loss treatment. In total, 51 participants completed diary assessments of weight stigmatizing events and reported how they felt and coped with each incident. Experiencing stigma was significantly associated with fewer positive and greater negative emotions. There was a significant inverse relationship between using positive self-talk and feeling numb and a positive relationship between using isolation/avoidance coping and feeling depressed, ashamed, and less happy. The significant negative momentary impacts of weight stigma likely contribute to the long-term negative consequences of experiencing weight stigma.